Intramasseteric spindle cell hemangioendothelioma: A rare case report with review of literature. Issue 4 (July 2018) - Singh, Gaurav; Mishra, Madan; Gaur, Amit; Tewari, Abhivyakti; Dewan, Udita; Parashar, Nidhi
Abstract: Spindle cell hemangioendothelioma (SCH) was first described in 1986 by Weiss and Enzinger as a vascular neoplasm, characterized by cavernous blood vessels and spindled areas reminiscent of Kaposi's sarcoma. The head and neck region is rarely involved with extremely rare muscular involvement; this being the first case of intramasseteric SCH. A 30 year old male presented with a 2-year history of a painless, slow growing swelling on the left side of face. Fine needle aspiration cytology and Magnetic Resonance Imaging revealed it to be a vascular malformation. As the lesion did not respond to intralesional sclerotherapy, the lesion was surgically excised under general anaesthesia. The final diagnosis was aided by histopathological analysis and immunohistochemistry which revealed the lesion to be an intramassteric spindle cell hemangioendothelioma. On reviewing the literature, it can be established that spindle cell hemangioendothelioma is an unusual vascular tumor of the head and neck that is important to recognize to avoid misdiagnosis. Immunohistochemistry is considered as the final diagnostic aid and local surgical excision has been the most accepted treatment modality.